Study of Consumer Preference Toward Food and Beverage Services Post COVID-19 Pandemic - Destriana, Odila Ivani (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to identify the determining factors of consumer preferences in choosing food and beverage services, especially restaurants and cafs, after the COVID-19 pandemic. The study was conducted using a mixed methodology, incorporating both qualitative and quantitative research methodologies. Qualitative research was conducted through focus group discussions with selected target markets to determine the factors that encourage consumers to visit certain restaurants and/or cafes. The insights gained from the FGDs were then used to develop questions in the questionnaire, which formed part of the quantitative research. The questionnaire was distributed online and received approximately 200 responses, which were subsequently processed using SPSS software. Three main factors determining consumer preferences for food and beverage services were identified in this research: consumer behavior, consumer motivation, and the role of social media. These factors were further analyzed and processed into key variables to better understand consumer preferences. It is hoped that the results of this research can provide strategic insights for restaurant and caf businesses to navigate changes in consumer behavior following the COVID-19 pandemic.